OC-056 AUTOIMMUNE/INFLAMMATORY SYNDROME INDUCED BY SYNTHETIC HERNIA MESH IN ADULTS – DESCRIPTION OF THE PATHOPHYSIOLOGY AND SYSTEMATIC REVIEW OF THE EVIDENCE. (13th October 2022) - Jíšová, B; Woleský, J; Střížová, Z; de Beaux, A; East, B
Abstract: Background: There is an increasing number of patients following hernia surgery with implanted mesh reporting symptoms that could indicate autoimmune or allergic reactions. 'Allergy' to metals, drugs, and chemicals is well recognised. However, allergy or autoimmunity caused by mesh has not been proven by a scientific method to date. The aim of this study was twofold: to describe the pathophysiology of autoimmunity and foreign body reaction and to undertake a systematic review of mesh implanted at the time of hernia repair and the subsequent development of autoimmune disease. Methods: A systematic review using the PRISMA guidelines was undertaken. Pubmed, Google Scholar, and Cochrane databases were searched for English-written articles published between 2000 and 2021. The search was performed using keywords "hernia", "mesh", "autoimmunity", "ASIA", "immune response", "autoimmune response" Results: Seven papers, were included in the final analysis – three systematic reviews, three cohort studies and one case report. Much of the current data regarding the association of hernia mesh and autoimmunity relies on retrospective cohort studies and/or case reports with limited availability of cofounding factor data linked to autoimmune disease. Three systematic reviews have discussed this topic, each with different approach and none of them has identified causality between the use of mesh and development of autoimmune disease. Conclusion: There is evidence that certain biomaterials can lead to immune dysregulation and induce autoimmunity. However, this has never been proven with synthetic hernia mesh. The bias in trials are high. And scientific studies have not been undertaken mesh-related autoimmunity.